Efficacy and tolerability of mogamulizumab in mycosis fungoides and Sézary Syndrome: a monocentric retrospective study - Giordano, Antonio; Fianchi, Luana; Criscuolo, Marianna; Quattrone, Martina; Di Pilla, Alessia; Pagano, Livio (Frontiers in Oncology, 2026)
BackgroundMycosis Fungoides (MF) is a common subtype of primary cutaneous T-cell lymphoma (CTCL), a group of non-Hodgkin lymphomas. The clinical spectrum of MF ranges from isolated cutaneous lesions to widespread involvement of lymph nodes, blood, and skin, as seen in its aggressive variant, Sézary Syndrome (SS). Mogamulizumab, a defucosylated humanized IgG1-κ anti-CCR4 monoclonal antibody approved for relapsed/refractory MF/SS, has demonstrated a favorable safety and efficacy profile in multiple case series.MethodsThis retrospective, monocentric observational study analyzed data from 12 patients treated with Mogamulizumab between January 1, 2019, and December 31, 2024. We aim to evaluate the tolerability and clinical response to Mogamulizumab in patients with MF/SS.ResultsOf the 12 patients treated, 8 had MF and 4 had SS. The median follow-up time was 29.9 months (range 2.8–68.6 months). Four patients discontinued mogamulizumab: 3 due to disease progression and 1 due to the development of breast cancer. Adverse events included MAR in 4 patients (33%) and colitis in 1 patient (6%). The observed median PFS after mogamulizumab therapy was 5.4 months, and the observed ORR was 50%. For all 12 patients, the median time to response (TTR) was 129 days. The observed median overall survival (OS) was 11.5 months, with 1 reported death due to septic shock in a patient who underwent salvage allo-HSCT after mogamulizumab failure.ConclusionsThe results of this study reaffirm the efficacy of Mogamulizumab therapy for patients with Mycosis Fungoides and Sézary Syndrome in a real-world setting, which involves treatment decisions that must often consider patient heterogeneity, comorbidities, and prior lines of therapy.